Recurrent spontaneous hepatic rupture in pregnancy: A case report. Issue 29 (July 2018) - Han, Gwan Hee; Kim, Min-A
Abstract: Rationale: Spontaneous and repeated hepatic ruptures caused by hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome are uncommon but life-threatening conditions that rarely occur early in the second trimester of pregnancy. Patient concerns: We describe a patient who experienced spontaneous hepatic ruptures in the absence of hypertension during the early second trimesters of both her first and second pregnancies. Diagnoses: A 34-year-old multiparous woman without hypertension was admitted at 21 weeks' gestation because of a spontaneous hepatic rupture with hemoperitoneum. Four years previously, the patient had undergone an exploratory laparotomy during her first pregnancy that involved the ligation of bleeders, because a hepatic capsule rupture had caused hemoperitoneum development. Interventions: Unlike the first pregnancy, she was managed nonsurgically and conservatively during the second pregnancy, and she underwent frequent laboratory analyses and magnetic resonance imaging follow-up. On day 11 of the patient's hospital admission, we decided to deliver the baby at 23 weeks' gestation, because her condition had deteriorated. Outcomes: Non-surgical management improved the patient's outcome, and the baby was born alive, even though the pregnancy was in the early second trimester and the maternal condition was deteriorating rapidly. Lessons: HELLP syndrome without hypertension and the recurrence of an intrahepatic rupture at an extremely premature gestational age are rare. This patient's findings suggested HELLP syndrome, which was subsequently diagnosed. This patient's clinical course highlights the difficult decisions made by clinicians for mothers and fetuses.